2014
DOI: 10.1002/hbm.22682
|View full text |Cite
|
Sign up to set email alerts
|

The mirror neuron system and the strange case of Broca's area

Abstract: Mirror neurons, originally described in the monkey premotor area F5, are embedded in a frontoparietal network for action execution and observation. A similar Mirror Neuron System (MNS) exists in humans, including precentral gyrus, inferior parietal lobule, and superior temporal sulcus. Controversial is the inclusion of Broca's area, as homologous to F5, a relevant issue in light of the mirror hypothesis of language evolution, which postulates a key role of Broca's area in action/speech perception/production. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 64 publications
4
29
0
Order By: Relevance
“…comparable cortical responsiveness to the same action in different modalities). In this vein, our data support the notion of abstract and multimodal sensory-motor representations of actions (Ionta, Sforza, Funato, & Blanke, 2013), including not only visual, auditory, and motor domains (Aglioti & Pazzaglia, 2011;Glenberg & Kaschak, 2002;Keysers, et al, 2003;Kohler, et al, 2002), but also speech processes (Cerri, et al, 2015;Rizzolatti & Arbib, 1998). The stronger brain activity in the action-related speech conditions with respect to the conditions in which a speech component was absent ("meaningless" orolingual movement control condition), provides evidence that this activation pattern cannot be explained by the mere motor activation due to the movements of mouth and tongue.…”
Section: Overlap Between Visuo-motor and Speech Oem Systems For Actionssupporting
confidence: 83%
See 1 more Smart Citation
“…comparable cortical responsiveness to the same action in different modalities). In this vein, our data support the notion of abstract and multimodal sensory-motor representations of actions (Ionta, Sforza, Funato, & Blanke, 2013), including not only visual, auditory, and motor domains (Aglioti & Pazzaglia, 2011;Glenberg & Kaschak, 2002;Keysers, et al, 2003;Kohler, et al, 2002), but also speech processes (Cerri, et al, 2015;Rizzolatti & Arbib, 1998). The stronger brain activity in the action-related speech conditions with respect to the conditions in which a speech component was absent ("meaningless" orolingual movement control condition), provides evidence that this activation pattern cannot be explained by the mere motor activation due to the movements of mouth and tongue.…”
Section: Overlap Between Visuo-motor and Speech Oem Systems For Actionssupporting
confidence: 83%
“…Indeed there have been many reports about (i) the activation of sensory-motor areas during speech processes (Aziz-Zadeh, Wilson, Rizzolatti, & Iacoboni, 2006;Boulenger, et al, 2008;Hauk, et al, 2004;Pulvermuller, 2005;Tettamanti, et al, 2005), (ii) the influence of speech processing on motor performance (Emmorey, 2013;Fischer & Zwaan, 2008;Nazir, Jeannerod, & Hauk, 2008), and (iii) the specific impairment in action-related words in patients suffering from diseases affecting the motor system (Bak, et al, 2001;Boulenger, et al, 2008). Based on these data it has been speculated that the human ability for speech may have evolved from pre-existing mechanisms dedicated to visuo-motor OEM for actions (Arbib, 2005;Cerri, et al, 2015;Corballis, 2003), proposing that multimodal action representations provide a simulation mechanism that may have evolved into representations of action goals, intentions, and language (D'Ausilio, Bartoli, & Maffongelli, 2015;Glenberg & Kaschak, 2002;Pulvermuller, 2005).…”
Section: Integrative and Multimodal Representations Of Movementsmentioning
confidence: 99%
“…Given the current interest and contentions in debates regarding MNS systems in the context of gestural origins behind the evolution of spoken language systems (Gallese and Goldman, 1998; Corballis, 1999; Arbib, 2005; Cerri et al, 2015), further study of the functional roles of the posterior insulae would be merited to address predictions made by anthropological theories. In particular, one theory hypothesizes that symbolic representations in the brain for specific natural categories, including “vocalizations” and “incidental sounds of locomotion” (in addition to “tool-use sounds”), reflect some of the earliest sound-producing categories of events that would need to have been effectively communicated orally by hominins (Hewes, 1992; Larsson, 2014, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The first stages of mirror neurons research identified individual brain regions with mirror neuron activity; progressively, research has begun to view the mirror neuron system (MNS) as an integrative network that communicates information across multiple regions of the brain. The MNS has been found associated with empathy,3 social reciprocation,4 verbal and non-verbal communication, language, and several others 5. These functions parallel symptoms observed in ASD 4.…”
mentioning
confidence: 76%